Study on tunnel ventilation and pollutant diffusion mechanism during construction period - Xiaoke Chang; Jianxi Ren; Rong Yang; Yan Tong (PLoS ONE, 2025)
Ventilation technology is an important means to ensure effective control of pollutant concentration and safe production during tunnel drilling and blasting construction. This study combines theoretical derivation, numerical simulation, and mathematical statistics to explore the extraction of flow field distribution characteristics and pollutant transport and diffusion mechanisms in tunnels. The research results indicate that the instability and turbulence effects of fluids work together to form a vortex zone near the tunnel working face. Fluid instability refers to the tendency of fluids to undergo changes under the influence of tunnel sidewalls or airflow in ducts. Turbulence effect is caused by the chaotic and irregular flow of fluids, leading to fluid mixing and rotation. The complex flow field changes inside the tunnel result in the retention of pollutants generated during construction in specific zone. The main reasons for the formation of pollutant stagnant zones are the bypass effect, low-velocity regions, and vortex of fluid. The emission process of pollutants can be divided into two stages: extraction and dilution. The dilution effect of pollutants is inversely proportional to the distance between the air duct and the working face, and the extraction amount is directly proportional to the airflow of the fan. The shorter distance allows fresh air to directly reach high concentration pollutant zone from the air duct, accelerating the mixing and dilution process. A larger airflow can provide stronger power and carry more pollutants out of the tunnel. The improved Technique for Order Preference by Similarity to an Ideal Solution method can optimize the layout of ventilation parameters and improve ventilation conditions. Finally, an empirical calculation formula for air supply volume is derived through in - depth research and data analysis. This formula takes into account multiple factors related to the tunnel structure, pollutant generation, and ventilation requirements. This empirical formula provides a scientific basis for the selection of ventilation fans in the construction preparation stage. Construction planners can accurately calculate the required air supply volume according to the specific situation of the tunnel, and then select the appropriate ventilation fan, which can not only ensure the ventilation effect but also save energy and reduce costs.